The effect of adding glucomannan derived from porang tuber extract (Amorphopallus onchophyllus) on dietary protein utilization in broiler chicken - Khanifah .; N. Suthama; H. I. Wahyuni (Jurnal Ilmu Ternak dan Veteriner, 2018)
The aims of this study was to evaluate the affect of dietary addition of glucomannan derived  from porang (Amorphophallus oncophyllus) tuber extract (GEUP) in broiler  ration on performance of broiler chicken. There  were 160 birds of day old broiler chicks of New Lohmann strain with average initial body weight of 42.08±0.86 g. The study was arranged in a completely randomized design with 5 treatments and 4 replications. Each replication consisted of 8 birds. The treatments applied were T0 = basal ration, T1 = T0 + 0.05% GEUP, T2 = T0 + 0.10% GEUP, T3 = T0 + 0.15% GEUP and T4 = T0 + 0.20% GEUP. The parameters observed were protein digestibility, nitrogen retention, meat calcium and protein mass. The results showed that dietary addition of GUEP significantly (P <0.05) increased coefficient of protein digestibility, meat calcium and protein mass, but had no affect on nitrogen retention. The highest protein digestibility and meat calcium mass were shown at T4, but  it was not significantly different from T3, and T2 for protein digestibility. While the highest meat protein mass was at T2 but it was not different with T3 and T4. The conclusion of the study was that dietary supplementation of  glucomannan derived from porang tuber extract in broiler up to 0.15% (T3) increased protein digestibility, meat calcium and protein mass with similar nitrogen retention.